Scalable cold-atom quantum simulator for two-dimensional QED - Ott, Robert; Zache, Torsten Victor; Jendrzejewski, Fred; Berges, Jürgen (Physical review letters, 2021)
We propose a scalable analog quantum simulator for quantum electrodynamics in two spatial dimensions. The setup for the U(1) lattice gauge field theory employs interspecies spin-changing collisions in an ultracold atomic mixture trapped in an optical lattice. We engineer spatial plaquette terms for magnetic fields, thus solving a major obstacle toward experimental realizations of realistic gauge theories in higher dimensions. We apply our approach to the pure gauge theory of compact QED and discuss how the phenomenon of confinement of electric charges can be described by the quantum simulator.
Gesehen am 15.12.2021